2005
DOI: 10.1186/1477-7525-3-14
|View full text |Cite
|
Sign up to set email alerts
|

Subjective impact of osteoarthritis flare-ups on patients' quality of life

Abstract: Background: Clinical trials on osteoarthritis (OA) flare-ups treatment usually focus only on objective measures of health status, albeit recent literature suggestions on the importance of patients' subjectivity. Aim of the study was to evaluate the effects of OA and of its different types of medical treatment(s) on Health Related Quality of Life (HRQoL) in terms of both subjective satisfaction and functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Although flare-ups have been studied in both inflammatory 3,4 and non-inflammatory rheumatic disease 5 , little is known about the characteristics of flare-ups of chronic nonspecific back pain (CNSBP). This lack of information is noteworthy, since multiple qualitative studies have confirmed that flare-ups are an important part of the experience of CNSBP for many patients 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Although flare-ups have been studied in both inflammatory 3,4 and non-inflammatory rheumatic disease 5 , little is known about the characteristics of flare-ups of chronic nonspecific back pain (CNSBP). This lack of information is noteworthy, since multiple qualitative studies have confirmed that flare-ups are an important part of the experience of CNSBP for many patients 68 .…”
Section: Introductionmentioning
confidence: 99%
“…The classic version of the VAS was administered: 10-centimeter line, horizontal. VAS on present pain ranged from “no pain” to “the worst pain possible” and VAS on pain relief ranged from “no pain relief” to “the maximum pain relief.” Scores ranged from 0 to 10 [13]. …”
Section: Methodsmentioning
confidence: 99%
“…The SF-36 [2] [3] [15] is a well-known self-administered and generic health status measure which encompasses 8 domains related to daily life activities and consist of 36 items. Each domain scores from 0 (lowest level of functioning) to 100 (highest level of functioning).…”
Section: Measurement Toolmentioning
confidence: 99%
“…Osteoarthritis (OA) is a chronic disease that has a substantial effect on patients' health related quality of life (HRQoL) as well as an extremely high economic burden usually attributed to the treatment side effects [1]. Activities of daily living are negatively affected in OA patients [2]. Its symptoms are debilitating, and accounting for significant disability characterized as the impaired performance of social and physical life tasks [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation